MILITARY LEADERSHIP AND LEADER PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL MILITARY BEHAVIOR - Yogaswara, Andrey Satwika; Ahman, Eeng; Disman, Disman; Nugraha, Nugraha (Faculty of Economic and Business, University of Pasundan, 2023)
This study aims to examine the effectiveness model of military leadership and organizational military behavior (OMB) on the organizational performance of the Indonesian National Armed Forces (TNI). This research uses descriptive and explanatory survey methods. The population in this study were 69 POMDAM and DENPOM units throughout Indonesia. The data collection technique uses cross-sectional techniques through Google Forms. The data analysis used is the Partial Least Square-Structural Equation Model. The findings of this study conclude: (1) the new concept has valid and reliable indicators; (2) military leadership and OMB significantly affect performance; (3) military leadership significantly affects organizational performance through OMB as mediation. Therefore, this research is expected to assist one of the crucial sectors in Indonesia and be considered in research in the military sector. Furthermore, the concepts and models in this study should be empirically tested in further research.